Chemical composition of the same brazilian propolis sample analyzed in 1997 and in 2012: No freezing effect - Conti, Bruno José [UNESP]; Bankova, Vassya; Sforcin, José Maurício [UNESP] (My University, 2015)
The same propolis sample that was analyzed by GC-MS in 1997 and 2012 was examined again after being frozen for 15 years. No qualitative changes were seen in its composition; artepilin C, prenyl-p-coumaric acid, dihydrocinnamic acid, caffeic acid were the major compounds.
Keywords: Gas Chromatography-Mass Spectrometry; Phenolics Compounds; Propolis